Valeria Añón (Coord.). 500 años de la Conquista de México. Resistencia y apropiaciones (Buenos Aires: Clacso, 2022), 381 pp - Nápoli, Tomás Santiago (2023)
Fil: Nápoli, Tomás Santiago. Pontificia Universidad Católica Argentina; Argentina